2007
DOI: 10.1128/aac.01551-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Isepamicin, Other Aminoglycosides, and Capreomycin against Clinical Isolates of Rapidly Growing Mycobacteria in Taiwan

Abstract: The in vitro activities of isepamicin against 117 Mycobacteria abscessus, 48 Mycobacterium fortuitum, and 20 Mycobacterium chelonae isolates were evaluated by a microdilution test. Isepamicin MIC 90 s were <16 g/ml for the three species. Isepamicin was as active as amikacin and kanamycin and more active than tobramycin, capreomycin, gentamicin, and streptomycin.Rapidly growing mycobacteria (RGM) can cause a wide spectrum of disseminated or localized diseases, especially pulmonary, skin, or soft tissue infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The inoculated plates were placed into plastic bags, incubated at 35°C in ambient air, and read after 72 h. The MIC was defined as the lowest concentration of drug that inhibited visible growth. Susceptibility was evaluated according to CLSI breakpoint recommendations (8,37) and those proposed previously by Shen et al (24).…”
Section: Methodsmentioning
confidence: 99%
“…The inoculated plates were placed into plastic bags, incubated at 35°C in ambient air, and read after 72 h. The MIC was defined as the lowest concentration of drug that inhibited visible growth. Susceptibility was evaluated according to CLSI breakpoint recommendations (8,37) and those proposed previously by Shen et al (24).…”
Section: Methodsmentioning
confidence: 99%
“…However, our analyses revealed that only 2 (18%) of 11 M. chelonae isolates were susceptible to tobramycin, whereas amikacin was active against 86% of them. The recent studies by FernandezRoblas et al [17] and Shen et al [18] also reported high susceptibility rates of M. chelonae to amikacin, although notably more than 80% of their isolates remained susceptible to tobramycin. The small number of M. chelonae isolates in our study precluded definitive conclusions; nonetheless, the observation that few isolates were tobramycin susceptible, coupled with the almost nonexistent use of this aminoglycoside in clinical practice locally, highlighted the need to review the value of routine testing of tobramycin activity against M. chelonae (and other RGM) species in our local setting.…”
Section: Discussionmentioning
confidence: 90%
“…Diseases caused by RGM are often difficult to treat and have a high rate of recurrence. This is especially true for infections caused by Mycobacterium abscessus, which are often intractable to antibiotic therapy [1]. Amikacin is the only drug recommended in the 2007 American Thoracic Society guidelines for treatment of RGM infections.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that the cyclic peptide capreomycin, which has been used to treat multidrug-resistant tuberculosis (MDR-TB), was effective against M. fortuitum but showed poor activity against M. abscessus and M. chelonae [1]. Other studies have indicated that clofazimine, dapsone and d-cycloserine are effective against MDR-TB, Mycobacterium kansasii, Mycobacterium avium complex (MAC) and Mycobacterium leprae [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation